EXPLORING THE ROLE OF MEDICAL AND OBSTETRIC FACTORS IN SEXUAL DYSFUNCTION AMONG POSTPARTUM WOMEN IN RIVERS STATE - Ibe , Chukwuemeka Oluwaseun (International Journal of Contemporary Health Sciences and Technology, 2024)
This study investigated the medical and obstetric determinant of sexual dysfunction among postpartum women in Rivers State. The study adopted descriptive research design with a population consisting of two million, six hundred and seventy thousand, nine hundred and three (2,670,903) postpartum women in Rivers State. A multi-stage sampling procedure was used to select a sample size of 1,200. Data was collected using an adapted questionnaire titled “Female Sexual Function Index (FSFI)” with a reliability coefficient of 0.856. The data collected were analyzed with the aid of Statistical Product for Service Solution (SPSS) version 23.0 linear and multinomial logistic regression at 0.05 alpha level. The finding of the study showed that there existed statistically significant relationship between sexual dysfunction and variables such as mode of delivery (p<0.05), history of hypertension (p<0.05), and history of diabetes (p<0.05). The findings of the study further established that majority 825(98.9%) of those who had Cesarean section had sexual dysfunction; all the respondents (100%) and majority (98.0%) who were hypertensive and diabetic respectively had sexual dysfunction. It was concluded that the determinants of sexual dysfunction among postpartum women in Rivers State were mode of delivery, history of hypertension, and history of diabetes. It was recommended that, the Rivers State healthcare board should help postpartum women to ease sexual health problems by establishing special sexual health units for postnatal mothers in every healthcare facility.